Pengembangan Model Turnamen Game Menyenangkan untuk Meningkatkan Motivasi dan Performa Pemain Tenis Menengah - Rizal Eka Wibisono; Hadi; Dewangga Yudhistira; Yudi Dwi Saputra; Franciska Dina Dameria (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The problem addressed in this study arises from intermediate-level tennis training sessions that tend to be repetitive and lack variation, leading to boredom, decreased motivation, and stagnant performance among players. This condition is further exacerbated by the limited integration of social and psychological aspects within conventional training methods. The purpose of this study is to design and evaluate the Fun Games Tournament (FGT) model as a more innovative and engaging training approach to enhance players’ motivation and performance. The research employed a 3D development model (Define, Design, Develop), which included needs analysis, model design, and development followed by expert validation using the Delphi technique. Content validity was assessed using Aiken’s V, while reliability was measured through Cronbach’s Alpha and the Intraclass Correlation Coefficient (ICC). The findings indicate that the FGT model demonstrates high validity (V = 0.80–0.95) and acceptable reliability (α = 0.606; ICC = 0.637; p = 0.010). Therefore, the FGT model is considered feasible and effective for improving motivation and performance in intermediate tennis players.